Flat Optical and Plasmonic Devices Using Area-Selective Ion-Beam Doping of Silicon - Salman, Jad; Hafermann, Martin; Rensberg, Jura; Wan, Chenghao; Wambold, Raymond; Gundlach, Bradley S.; Ronning, Carsten; Kats, Mikhail A. (Advanced Optical Materials, 2018)
Highly doped semiconductors are an emerging platform for plasmonic devices. Unlike in noble metals, the carrier concentration of semiconductors can vary by many orders of magnitude, resulting in a widely tunable range of plasma wavelengths spanning the mid-infrared and terahertz ranges. In this work, the potential of highly doped, ion-beam-patterned silicon is demonstrated as a fabrication-friendly platform for flat optical devices. Detailed characterization of the optical properties of silicon is performed at various doping levels, and diffractive optical elements and plasmonic frequency-selective surfaces that operate in the mid-to-far-infrared regime are realized. The resulting optical devices are monolithic, flat, resilient to thermal and physical damage, and can be easily integrated into other silicon-based platforms.
CRIS-Team Scopus Importer:2023-04-20
Keywords: diffractive optics; ellipsometry; embedded optics; infrared optics; plasmonics; semiconductor materials